2017
DOI: 10.3892/or.2017.5418
|View full text |Cite
|
Sign up to set email alerts
|

ELF5 in epithelial ovarian carcinoma tissues and biological behavior in ovarian carcinoma cells

Abstract: The expression of E74-like factor 5 (ELF5) in epithelial ovarian carcinoma tissues and its effects on biological behavior in ovarian carcinoma cells were assessed in search for a new approach for gene treatment of epithelial ovarian carcinoma. RT-PCR technology was applied to detect the expression of ELF5 mRNA in epithelial ovarian carcinoma (n=49), borderline ovarian epithelial tumor (n=19), benign ovarian epithelial tumor (n=31) and normal ovarian tissues (n=40). Then, we transfected recombinant plasmid pcDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The majority of evidence generated to date indicates ELF5 plays a tumour suppressive role in prostate [ 59 , 60 ], bladder [ 61 ], ovarian [ 62 ] and renal cancer [ 63 ]. In prostate cancer, loss of ELF5 protein expression correlates with loss of expression of the epithelial marker E-Cadherin and increased expression of the mesenchymal marker N-Cadherin [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of evidence generated to date indicates ELF5 plays a tumour suppressive role in prostate [ 59 , 60 ], bladder [ 61 ], ovarian [ 62 ] and renal cancer [ 63 ]. In prostate cancer, loss of ELF5 protein expression correlates with loss of expression of the epithelial marker E-Cadherin and increased expression of the mesenchymal marker N-Cadherin [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, ELF5 mRNA expression in ovarian cancer [ 62 ] and ELF5 mRNA and protein in renal cell carcinoma [ 63 ] is reduced compared to corresponding normal tissue, and re-expression of ELF5 in cell line models of these cancers inhibits cell proliferation and survival [ 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Ormandy (10) showed that the E3 domain of Elf5 is rich in proline and has protein binding function, while the WW1 domain in the WWOX protein binds to a proline-rich domain, and the WWOX protein interacts with the transcription factor Elf5 through this property. The transcription factor Elf5 is not only involved in cell development, differentiation and apoptosis, but also regulates cell proliferation and tumorigenesis (11). Yan et al (12) showed that WWOX mRNa expression in ovarian cancer tissues was lower than that in normal ovarian tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al (12) showed that WWOX mRNa expression in ovarian cancer tissues was lower than that in normal ovarian tissue. Yan et al (11) showed that the expression of Elf5 mRNa in ovarian cancer tissues was lower than that in normal ovarian tissues. In this study, the expression of WWOX and Elf5 in 300 ovarian cancer tissues and adjacent normal tissues were detected by immunohistochemical method.…”
Section: Discussionmentioning
confidence: 99%
“…It might inhibit the invasion and metastasis of ovarian cancer cells by regulation of matrix metalloproteinase-2 (MMP-2) and MMP-9. In this way, it accelerates cell cycle and apoptosis by increasing the expressions of P21 and caspase-3 in the human ovarian cancer tissues ( 12 14 ). However, in endometrial carcinoma, the effects of ELF5 have not been fully revealed.…”
Section: Introductionmentioning
confidence: 99%